The Role of Social Market Economy Mechanisms in Promoting Iraq’s Accession to the World Trade Organization - Wazni, Adil Issa Kadhim; Hameed, Ammar Mahmood (International Journal of Psychosocial Rehabilitation, 2020)
This paper interesting on the issue of Iraq's accession to the World Trade Organization and the importance of laying the foundations and mechanisms for a successful, social market economy in order to enhance the accession process on sound foundations and make the most of correcting what is acceptable the economic path in a multilateral framework and removing Iraq from international commercial and economic isolation, with investment The mechanisms and components of the market economy in support of the transformation programs in the Iraqi economy and the acceleration of the process of joining the World Trade Organization by overcoming the obstacles that prevent this and establishing the relationship between the social market economy and the attempts made by the government to join the World Trade Organization as a framework for action to advance the economy The Iraqi forward is far from the rentier situation in its only direction of converting oil dollars into imports in the other words.